2001
DOI: 10.1002/ijc.1363
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin-induced apoptosis of mesothelioma cells is affected by potassium ion flux modulator amphotericin B and bumetanide

Abstract: Key words: amphotericin B; apoptosis; bumetanide; carboplatin; cisplatin; cytotoxicity; potassium channelsThe efflux of ions, primarily potassium ions, plays an important role during the induction of apoptosis. Apoptosis with ensuing reduction in cell volume is enhanced under conditions when the intracellular K ϩ concentration is diminished, and only shrunken cells with reduced K ϩ exhibit DNA fragmentation and elevation of caspase-3-like activity-hallmarks of apoptosis. 1 Increased inward pumping of potassium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 26 publications
0
41
0
1
Order By: Relevance
“…Not any of the exposures induced membrane blebbing or protrusion in the P31res1.2 cells. These concentrations also have similar inhibitory effects on NKCC1 activity in the P31 cells [16,19,35] demonstrating that there was little risk of non-specific effects of bumetanide regardless if 10 or 100 µmol/L bumetanide were used in the experiments.…”
Section: Abrogation Of Nkcc1 Activity Inhibits Early-phase Cisplatin-mentioning
confidence: 76%
“…Not any of the exposures induced membrane blebbing or protrusion in the P31res1.2 cells. These concentrations also have similar inhibitory effects on NKCC1 activity in the P31 cells [16,19,35] demonstrating that there was little risk of non-specific effects of bumetanide regardless if 10 or 100 µmol/L bumetanide were used in the experiments.…”
Section: Abrogation Of Nkcc1 Activity Inhibits Early-phase Cisplatin-mentioning
confidence: 76%
“…Recent studies have provided substantial evidence that potassium channels are involved in the regulation of tumor cell proliferation, acquirement of invasive, metastatic ability, apoptosis, cell cycle and even drug resistance (4,6,25,26). Among these potassium channels, HERG has demonstrated the strongest relationship with human cancer, and been considered as a potential therapeutic target (25,27).…”
Section: Discussionmentioning
confidence: 99%
“…Like most chemotherapeutic drugs, cisplatin exerts its anti-cancer effect by inducing apoptosis, probably mediate through caspase-3 activity (3). Cytotoxicity of cisplatin, and its ability to induce cancer cell apoptosis is influenced by modulators of potassium ion flux (4).…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, bumetanide, a specific inhibitor of NKCC, can inhibit the evolution of the apoptotic process [18,23,24]. Moreover, Bortner et al [3] showed that an increase in intracellular Na + precedes the apoptotic volume decrease, and intracellular Na + is a potent stimulus of outward cotransport [11].…”
Section: Discussionmentioning
confidence: 97%
“…More recently NKCC has been implicated in other physiological phenomena such as cell division [5,28,29,30] and apoptosis [18,23,24], where a volume increase or decrease respectively seems necessary to allow such processes to occur.…”
Section: Introductionmentioning
confidence: 99%